CFD Modeling of Biomass Thermal Conversion in A Novel Solar-Thermal Reactor - Ahmed, Rania (2020)
A Master of Science thesis in Chemical Engineering by Rania Ahmed entitled, “CFD Modeling of Biomass Thermal Conversion an A Novel Solar-Thermal Reactor”, submitted in May 2020. Thesis advisor is Dr. Yassir Makkawi. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).